Vocabulary and Grammar Mastery On The Writing Ability of College Students - Lestari, Pritantina Yuni; Mustain, Kun; Safitri, Isnaini Nur (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Writing is essential because it is used extensively in higher education and in the workplace. The aim of this study is to know whether there is a positive and significant correlation between vocabulary and grammar mastery in the writing ability of college students. It uses a correlational research design. The study was conducted at the Business Administration Department of the State Polytechnic of Malang, especially the English Study Program. These 53 students became the sample of the research. The writing test allowed the students to write an academic article consisting of 300-500 words. The result was there is a positive and significant correlation between students’ grammar mastery and writing ability, but not for students’ vocabulary mastery. The students should increase their vocabulary more to increase their writing ability.